Collaborative Transport Strategy for Dual AGVs in Smart Ports: Enhancing Docking Accuracy in No-Load Formations - Qiang Zhang; Wenfeng Li; Long Guo; Xiaohang Qi (Journal of Marine Science and Engineering)
To enhance the adaptability of automated guided vehicles (AGVs) in port operations, this paper proposes a novel collaborative transport strategy for dual AGVs. This study focuses on reducing formation completion time, improving motion safety, and enhancing pose accuracy at the docking point for no-load dual AGVs, which is the first phase of the transport strategy. To implement this strategy, the sizes of the existing AGVs are adjusted, and a hybrid collaborative control framework is designed. This framework includes a feedback mechanism based on the leader–follower formation model, along with a closed-loop controller utilizing the sliding mode control algorithm. Finally, simulation and physical tests based on real port data verify the proposed strategy’s effectiveness. The results show it significantly enhances the dual AGVs’ motion safety and docking accuracy, providing new insights for smart port development.